Isolation, characterization and therapeutic evaluation of phage HHU1 against K2 Klebsiella pneumoniae - Han, Pengjun; Sun, Shuting; Wen, Liwen; Yang, Lei; Li, Enzhong; Yang, Yang (Frontiers in Cellular and Infection Microbiology, 2025)
The prevalence of multidrug-resistant Klebsiella pneumoniae (K. pneumoniae) poses a severe threat to the global economy and public health, driving a resurgence of interest in phage therapy. Consequently, it is imperative to isolate lytic phages against K. pneumoniae with potent bactericidal activity. This study reports the isolation and characterization of the phage HHU1 against K. pneumoniae from hospital sewage, to evaluate its potential for phage therapy. Phage HHU1 has an icosahedral head and retractable tail, similar to members of the Jedunavirus genus. Host range tests revealed that phage HHU1 obligately lysed K. pneumoniae of the K2 serotype. Genome sequencing analysis showed that the genome of phage HHU1 was 47,779 bp in length, with a GC content of 49.2%, encoding 78 open reading frames, and lacked genes associated with lysogeny and virulence. The rapid adsorption (8 min), short latent period (10 min), and high burst size (approximately 134 PFU/cell) indicate robust replication kinetics of phage HHU1. Phage HHU1 remained stably active even after incubation for 6 h at pH 5.0-10.0 and temperature 4-40°C. In addition, phage HHU1 with different MOIs can completely inhibit the growth of drug-resistant K. pneumoniae within 8 h in vitro and significantly reduce biofilm formation of drug-resistant bacteria. Notably, treatment with high-dose phage HHU1 (MOI = 0.1 and 1) achieved 100% survival in Galleria mellonella larvae infected with drug-resistant K. pneumoniae. These findings demonstrate the potential of phage HHU1 as a promising therapeutic candidate against drug-resistant K. pneumoniae infections.